The fiscal and intergenerational burdens of brakes and subsidies for energy prices - Christian Scharrer; Johannes Huber (Universität Augsburg, Institut für Volkswirtschaftslehre, 2023)
We study the effects of different financing rules for untargeted energy price brakes and subsidies on intergenerational welfare in a large-scale overlapping generations model. The results indicate that, in comparison to a laissez-faire solution without any government interventions, debt-financed implementations of such measures are very detrimental for young and future generations. However, the taxation of windfall profits can significantly contribute to reduce the economic burdens of these generations, whereas the positive effects on older generations are much less pronounced.
urn:nbn:de:bvb:384-opus4-1139491
Keywords: E62; E30; H20; H30; 330; Fiscal Policy; Price Brakes; Price Subsidies; Energy Crisis; Welfare